2010
DOI: 10.1002/humu.21257
|View full text |Cite
|
Sign up to set email alerts
|

Stickler syndrome and the vitreous phenotype: mutations in COL2A1 and COL11A1

Abstract: Stickler syndrome is a dominantly inherited disorder affecting the fibrillar type II/XI collagen molecules expressed in vitreous and cartilage. Mutations have been found in COL2A1, COL11A1 and COL11A2. It has a highly variable phenotype that can include midline clefting, hearing loss, premature osteoarthritis, congenital high myopia and blindness through retinal detachment. Although the systemic phenotype is highly variable, the vitreous phenotype has been used successfully to differentiate between patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 20 publications
6
122
0
2
Order By: Relevance
“…14 Clinical assessment continues to have a vital role as an indicator of clinical suspicion and also to assist in indicating which genes to screen. 15 For the ophthalmologist, combining clinical and molecular genetic analysis is particularly important given the emerging array of ocular-only variants 10,11 (see below) with a high risk of retinal detachment, but Other Unknown Hypoplastic vitreous, deafness, arthropathy, cleft palate.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…14 Clinical assessment continues to have a vital role as an indicator of clinical suspicion and also to assist in indicating which genes to screen. 15 For the ophthalmologist, combining clinical and molecular genetic analysis is particularly important given the emerging array of ocular-only variants 10,11 (see below) with a high risk of retinal detachment, but Other Unknown Hypoplastic vitreous, deafness, arthropathy, cleft palate.…”
Section: Diagnosismentioning
confidence: 99%
“…38 In addition to assisting the clinical diagnosis, the diagnostic protocol depicted in Figure 2 assists and directs mutation analysis substantially improving COL2A1 analysis resulting in a 95% positive pick-up rate. 15,39 The advances currently being made in sequencing technologies, so-called next-generation sequencing, may in future make it more economically viable to sequence and analyse all candidate genes simultaneously; however, at present, the vitreous phenotyping before molecular analysis greatly increases the efficiency of mutation detection.…”
Section: Genetics and Molecular Mechanisms For Phenotypic Variationmentioning
confidence: 99%
“…7,8 Both are multi-exon genes with a large number of characterised mutations, many of which affect consensus splice sites. [9][10][11][12] Stickler syndrome can present with high myopia, midline clefting, midfacial hypoplasia, hearing loss, premature osteoarthritis and a high incidence of retinal detachment. 13 With an incidence of between 1 in 7500-1 in 9000 newborns, 14 it is phenotypically highly variable both between and within families, and patients often remain undiagnosed for many years, until the suggestion of the condition is raised clinically and later confirmed by genetic testing.…”
Section: Introductionmentioning
confidence: 99%
“…This variant was already observed in several Stickler cases. 9,[12][13][14] Finally, p.(Arg989Cys), c.2965C4T was carried by one of our SEMD Strudwick patients, and this variant has been previously reported in several SEDC cases. 9,[15][16][17] In accordance with the literature, we observed that arginine to cysteine changes were associated with a broad spectrum of diseases, but they were more often encountered in the moderate phenotypes.…”
Section: Discussionmentioning
confidence: 54%
“…Molecular defects in the COL2A1 gene (MIM#108300), which encodes the alpha 1 chain of procollagen type II, result in skeletal, 12 Service de Génétique, CHU Félix Guyon, Saint-Denis, La Réunion, France; 13 Service de Génétique, CHU de Nancy, Nancy, France; 14 Génétique Médicale, CHU, Nantes, France; 15 Service de Biologie du Développement, Hôpital Robert Debré, Paris, France; 16 Centre de Génétique, CHU Dijon -Hôpital d'Enfants, Dijon, France; 17 Département de Génétique Médicale, CHU de Nice -Hôpital de l'Archet II, Nice, France; 18 Unité de Génétique Clinique, CHU de Rouen -Hôpital Charles Nicolle, Rouen, France; 19 Génétique Médicale, CHU de la Réunion, Saint Pierre, La Réunion, France; 20 orofacial, and ocular disorders. These dominantly inherited diseases are associated with various COL2A1 variants that include missense, nonsense, small indels or large deletions.…”
Section: Introductionmentioning
confidence: 99%